Studi Pembuatan dan Karakteristik Sifat Mekanik dan Hidrofobisitas Bioplastik dari Pati Sorgum - Darni, Yuli; Utami, Herti (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2009)
This research investigated the utilization of sorghum starch and chitosan as basic material for preparation of biodegradble plastic. The optimum conditions for the formation of biodegradble plastic and the effect of starch-chitosan formulation on mechanical properties of the biodegradable plastic were studied. The experiments were conducted by varying concentration sorbitol as plasticizer (i.e. 20%, 25%, 30%, and 40% dry weight), ratio starch to chitosan (i.e. 6:4, 7:3, 8:2, 9:1, 10:0 g/g) and at ranging gelatinuous temperature of 65-95oC. The results showed that the optimum conditions were obtained at starch:chitosan mass comparison of 7:3 and sorbitol concentration of 20%. The mechanical properties of the biodegradable plastic produced at gelatinuous temperature of 95oC were: tensile strength of 6,9711 Mpa, elongation percentage of 16,48, modulus young of 42,48 Mpa, and water resistance of 36,825%.Keywords: bioplastic, chitosan, plasticizer, sorgum, sorbitol